Endometriosis Severity and Risk of Preeclampsia: A Combined Mendelian Randomization and Observational Study - Zu Y; Xie Y; Zhang H; Chen L; Yan S; Wang Z; Fang Z; Lin S; Yan J (International Journal of Women's Health)
Yizheng Zu,1– 4,* Yi Xie,1– 4,* Huale Zhang,1– 4,* Lichun Chen,1– 4 Shihan Yan,1 Zhenna Wang,1 Zhuanji Fang,1– 4 Shunhe Lin,1 Jianying Yan1– 4 1College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University Fujian Maternity and Child Health Hospital, Fuzhou, Fujian Province, People’s Republic of China; 2Fujian Clinical Research Center for Maternal-Fetal Medicine, Fuzhou, Fujian Province, People’s Republic of China; 3Laboratory of Maternal-Fetal Medicine, Fujian Maternity and Child Health Hospital, Fuzhou, Fujian Province, People’s Republic of China; 4National Key Obstetric Clinical Specialty Construction Institution of China, Fuzhou, Fujian Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shunhe Lin, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University Fujian Maternity and Child Health Hospital, No. 18 Daoshan Road, Gulou District, Fuzhou City, Fujian Province, People’s Republic of China, Email lsh2816@sina.com Jianying Yan, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University Fujian Maternity and Child Health Hospital, No. 18 Daoshan Road, Gulou District, Fuzhou City, Fujian Province, People’s Republic of China, Email yanjyfjmu@163.comPurpose: Endometriosis has been hypothesized to increase the risk of preeclampsia (PE) and eclampsia, although the exact mechanism of this relationship is not clear. This study aimed to further explore the potential association between endometriosis and PE/eclampsia through Mendelian randomization (MR) and confirm these findings in a retrospective cohort study.Methods: A two-sample MR study was performed using genetic variants associated with endometriosis from the Finnish database, with outcome data for PE and eclampsia from the UK Biobank. Subgroup analyses were conducted based on endometriosis severity (American society of reproductive Medicine (ASRM) stages I–II and III–IV) and anatomical location (uterus, ovary, deep infiltrating endometriosis). Additionally, a retrospective cohort study was conducted to further assess the association, adjusting for confounding factors such as age, Body Mass Index (BMI), dysmenorrhea, history of uterine surgery, and adenomyosis. Multivariate logistic regression was used to analyze the risk of PE/eclampsia based on endometriosis severity.Results: MR using the Inverse Variance Weighted method found a meaningful association between advanced endometriosis (ASRM stages III–IV) and PE/eclampsia (p = 0.008), while no significant associations were observed for lower stages or endometriosis in the uterus and ovary. In the retrospective cohort, the initial association between the revised American Fertility Society (r-AFS) score and PE/eclampsia (OR: 1.02, 95% CI: 1.01– 1.03, p < 0.001) weakened after adjusting for confounders. Significant risk factors identified included age (OR: 1.20, 95% CI: 1.10– 1.30, p < 0.001), dysmenorrhea (OR: 2.72, 95% CI: 1.31– 5.76, p = 0.008) and adenomyosis showing the strongest association (OR: 9.96, 95% CI: 5.00– 20.06, p < 0.001).Conclusion: The findings suggest a potential relationship between advanced endometriosis and the risk of PE/eclampsia. However, other clinical factors such as age, dysmenorrhea, and adenomyosis appear to contribute more significantly to the risk. Further studies are needed to confirm these findings and clarify the underlying mechanisms.Keywords: endometriosis, preeclampsia, Mendelian randomization, retrospective cohort, adenomyosis, dysmenorrhea